2022
DOI: 10.1016/s2213-8587(21)00292-8
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin in the treatment of heart failure with reduced ejection fraction in addition to background therapies and therapeutic combinations (EMPEROR-Reduced): a post-hoc analysis of a randomised, double-blind trial

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…These results may be extended to the other SGLT2 inhibitors that showed as beneficial in HFrEF, dapagliflozin and empagliflozin. These drugs were not discontinued during hospitalizations for HF in DAPA‐HF or EMPEROR‐Reduced and their efficacy was independent of concomitant therapy 39–41 …”
Section: Sodium–glucose Co‐transporter 2 Inhibitors As First‐line The...mentioning
confidence: 99%
See 2 more Smart Citations
“…These results may be extended to the other SGLT2 inhibitors that showed as beneficial in HFrEF, dapagliflozin and empagliflozin. These drugs were not discontinued during hospitalizations for HF in DAPA‐HF or EMPEROR‐Reduced and their efficacy was independent of concomitant therapy 39–41 …”
Section: Sodium–glucose Co‐transporter 2 Inhibitors As First‐line The...mentioning
confidence: 99%
“…These drugs were not discontinued during hospitalizations for HF in DAPA‐HF or EMPEROR‐Reduced and their efficacy was independent of concomitant therapy. 40 , 41 , 42 …”
Section: Sodium–glucose Co‐transporter 2 Inhibitors As First...mentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed results of the EMPEROR-Reduced trial are showed in Table 2. The benefits from empagliflozin therapy in terms of the primary endpoint risk reduction were independent of concomitant presence of diabetes type 2, left ventricular EF (LVEF), aetiology of HF, standard HF care in terms of drug classes (including ARNI) and doses used [6], and device therapy (ICD/CRT) used, which indicates a complementary effect of empagliflozin in addition to other HFrEF therapies, and the possibility of initiating this treatment at any stage of HF therapy. The benefits were also independent of the severity of clinical symptoms as measured by the NYHA class but were higher in lower NYHA class (i.e., class II) [2].…”
Section: Table 1 Main Inclusion and Exclusionmentioning
confidence: 99%
“…Empagliflozin may be added to any HF therapy [6], including both drug and device therapy, and regardless of the other drug doses used. According to the SPC, the recommended dose of empagliflozin in HF is 10 mg once daily.…”
Section: How To Initiate Empagliflozin Therapy?mentioning
confidence: 99%